Nighttown - Hallinan, Timothy (A Junior Bender mystery, 2018)
"Los Angeles burglar Junior Bender has a rule about never taking a job that pays too well--in the criminal underworld, if someone is offering you more money than a job is worth, someone is going to end up dead. But he's bending his rule this one time because he and his girlfriend, Ronnie, are in desperate need of cash so they can hire a top-notch kidnapper to snatch Ronnie's two-year-old son back from her evil ex. The whole thing is pretty complicated, and has Junior on edge. The parameters of his too-well-paying job do nothing to calm his nerves. A nameless woman in an orange wig has offered Junior fifty grand--twenty-five up front--to break into the abandoned house of a recently deceased 97-year-old recluse, Daisy Horton, and steal a doll from the woman's collection. Junior knows no doll is worth $50k, so he figures there must be something hidden inside the doll that can get him in a heap of trouble. It takes Junior less time than he would have hoped to realize he's not the only person looking for the doll. When an old friend ends up murdered, Junior decides he will stop at nothing to figure out who the woman in the orange wig is, and why she wants the doll so bad she's leaving a trail of bodies in her wake"--